Seed Dormancy Breaking Techniques of Two Species of Rattan in Central Sulawesi’s Mainstay: Daemonorops robusta Warb.ex Beccari and Calamus inops Beccari ex Heyne - Retno Agustarini; Diana Prameswari (Jurnal Perbenihan Tanaman Hutan, 2020)
Noko rattan (Daemonorops robusta) and tohiti rattan (Calamus inops) are the Sulawesi local rattans that are not yet cultivated due to obstacles in its cultivation techniques, especially in seed germination. The purpose of this study was to determine the breaking of dormancy of rattan noko and tohiti seeds. The treatments used are: control, scarification, soaked in the water for 24 hours, soaked in the mono sodium glutamat solution for 24 hours, and soaked in coconut water for 24 hours. The experimental design was completely randomized design. The parameters observed were the initial moisture content of the seed, the first day of germination, germination capacity, germination rate and germination value. The results show that both rattans seeds are recalcitrant. Noko rattan is easier to germinate than Tohiti rattan and the best treatment of dormancy breaking was used immersion with coconut water. In noko rattan, broken dormancy of the 13th day with germination capacity of 91.98%, mean germination time of 32.92 days and a germination value of 0.001. Tohiti rattan was able to break dormancy in the 29th day with 88.67% of germination capacity, 58.63 days of mean germination time and 0.001 of germination value.